Microsecond molecular dynamics simulations reveal the allosteric regulatory mechanism of p53 R249S mutation in p53-associated liver cancer. (February 2020) - Liu, Xianxian; Tian, Wenchao; Cheng, Jinying; Li, Dongmei; Liu, Tonggang; Zhang, Liguo
Highlights: MD simulations were performed to explore the allosteric effect of the R249S mutation on the p53 DBD. R249S mutation allosterically affects the S1-S2 turn at the DNA-binding interface. 3. The results can decipher the allosteric regulatory mechanism induced the R249S mutation. Abstract: The tumor suppressor p53, a transcription factor, plays a critical role in many cellular processes, including DNA repair and apoptosis and cell cycle arrest. Missense mutations in the p53 have closely related to human cancer. R249S mutation at the p53 core DNA binding domain (DBD) is frequently observed in hepatocellular carcinoma. This mutation is away from the p53 DBD-DNA binding interface. However, how the R249S mutation causes the structural changes of p53 DBD that lead to weak the binding of p53 mutant to DNA has not been clearly understood. Here, microsecond-scale molecular dynamics (MD) simulations of p53 DBD in the wild type (WT) and R249S mutated states in the absence of DNA binding were performed to explore the effect of the R249S mutation on the conformational dynamics of p53 DBD. The R249S mutation does not cause the global conformational changes, and it only affects the local domains at the mutation site and the DNA binding interface, particularly at the S1-S2 turn. The allosteric effects of the S1-S2 turn induced by the R249S mutation lead to the extension of the S1-S2 turn into the β-strands, which in turn interferes with the binding of DNA at the major groove. The results can help decipher the allosteric regulatory mechanism by which the R249S mutation of p53 DBD affects the p53 DBD-DNA interactions.